When the secret is “that” secret: negotiations and tensions between sexuality and religion in the biography of “Pancho” - Leal, Lucas Edgardo (2019)
Over the last few decades, in our country, there have been many significant changes related to the sociability and visibility of the LGBTI+ community, with laws that place it in the legislative vanguard with the recognition of demands regarding sexual rights and full citizenship for identities which are self-perceived as non-heterosexual. This path of state recognition has not been supported by the leadership of the Catholic church, which continues, in its discourses and practices, to stigmatize, pathologize and morally condemn sexualities self-perceived as non-heterosexual. However, beyond these discourses and practices opposed to the recognition of sexualities self-perceived as non-heterosexual, many self-identified gay individuals experience their faith in the institutionalized context of the Catholic church. In this paper I explore, with excerpts from an interview, the strategies of visibility/invisibility and institutional belonging to the Catholic church.